Determination of lipase inhibitory compound from Aquilaria Malaccensis matured leaves extract via pretreatment using bath sonicator: effect of sonication temperature: article - Mohd Shah, Nurul Aqilah; Ku Hamid, Ku Halim; Mohd Rodhi, Miradatul Najwa (2017)
The total phenolic and flavonoid compound contained in a plant named Aquilaria Malaccensis (A. malaccensis) was used as anti- obesity agent. In this research, lipase inhibitory compound was extracted from the selected dried matured leaves of A. malaccensis by pre- treatment method using bath sonicator with the temperature and ground sample sizes were set as the manipulated variables. With different ranges 40oC to 80oC of temperature and three ground leaves size 250µm, 500µm and 1000µm used, the effect and optimum parameters on recovery process can be determined. Mastersizer was used to measure the particle size and determine the optimum temperature. The concentration of phenolic and total flavonoid content contained in the samples at optimum sonicationtemperature was analysed by HPLC where gallic acid and quarcetin were set as the indicator. In conclusion, the optimum parameters to yield high phenolic and flavonoid compounds was discovered at 500μm of ground size and 60oC sonication temperature which have 1530µm of particle size.